The Impact of Type 2 Diabetes on Women’s Health and Well-being During Their Reproductive Years: A Mixed-methods Systematic Review - Celik, Aycan; Forde, Rita; Racaru, Simona; Forbes, Angus; Sturt, Jackie (Current Diabetes Reviews, 2022)
Background: The incidence of Type 2 Diabetes (T2DM) among younger women now accounts for 40% of females with T2DM. Women of reproductive age with T2DM have additional health considerations and their needs may differ from older populations. Objectives: The aims were (1) to identify the health issues encountered by women aged 16-45 years living with T2DM; (2) to determine the modifiable risk factors associated with living with diabetes; (3) to specify ideas for interventions to meet age and gender-specific diabetes-related healthcare needs. Methods: A systematic search was performed in the following databases; MEDLINE, PsycINFO, EMBASE, CINAHL, Web of Science, and Maternity and Infant Care. Databases were searched without time and study design limits. The Mixed Methods Appraisal Tool was used to assess the methodological quality of included studies. Data were narratively synthesised due to mixed methods evidence included. Results: A total of 32 papers were included in the review from which six domains were identified from the synthesis: (1) diabetes related modifiable risk factors: blood glucose, cardiovascular risk, neuropathy/nephropathy/retinopathy, diabetes self-management barriers (2) reproductive health: diabetes care before pregnancy, pre-pregnancy care barriers and expectations of women, contraceptive use (3) psychosocial wellbeing: depression symptoms and diabetes distress, perception of T2DM, emotional concerns about pregnancy (4) sexual function; (5) menopause; (6) sociocultural factors: social support, cultural norms. Conclusion: This review highlighted specific health issues affecting women of reproductive age with T2DM and which represent an important focus for health services research and health care delivery. Future research needs to address identified health domains to improve women’s health and well-being living with T2DM.
Keywords: healthcare needs